2020
DOI: 10.5539/gjhs.v12n10p122
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Conventional Medicine and Herbal Medicine Usage Amongst Diabetic Patients: A Qualitative Study in Negeri Sembilan, Malaysia

Abstract: INTRODUCTION: The concomitant intake of herbal medicine and conventional medicine amongst patients is steadily increasing worldwide. However, concerns have been raised regarding potential adverse effects and drug interactions when consuming both medications together. Therefore, this work aimed to comprehending the perception of Type 2 Diabetic Mellitus (T2DM) patients on conventional medicine and the manner of its use with herbal medicine in managing diabetes mellitus. METHODS: A qualitative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Changes in dietary behavior were also noted during CMCO. The dietary behavior among Malaysians changed during the stay-at-home order in terms of increased frequency of eating (46.5%), increased sugar-sweetened drink intake (27.7%), and increased fast/instant food intake (18.1%) compared with usual (Ithnain et al, 2020 ). Thus, it might explain why there were no significant differences in fasting blood glucose at the pretest and posttest comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in dietary behavior were also noted during CMCO. The dietary behavior among Malaysians changed during the stay-at-home order in terms of increased frequency of eating (46.5%), increased sugar-sweetened drink intake (27.7%), and increased fast/instant food intake (18.1%) compared with usual (Ithnain et al, 2020 ). Thus, it might explain why there were no significant differences in fasting blood glucose at the pretest and posttest comparison.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similarly, two local online surveys in Malaysia in April and July 2020 about health and social behaviours showed that approximately 50-60% of respondents were still meeting in person and socializing with friends and relatives during the Movement Control Order, which was put in place to slow the spread of COVID-19. 33, 34 Findings from these studies might explain why household-social and social transmission were the primary modes of early transmission in the community, educational institutions, religious organizations, workplace settings and among high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in the health care system and increased awareness about the importance of conventional medicines have seen many Malaysians seek treatments using conventional drugs. However, many are still taking herbal medicines together with conventional drugs (Basri et al 2022, Ithnain et al 2020.…”
Section: Introductionmentioning
confidence: 99%